Die Neue Planungskultur in der Regionalentwicklung — eine Spurensuche - Ludwig, Jürgen (Raumforschung und Raumordnung | Spatial Research and Planning, 2005)
The aim of this study is to answer the question of whether the new planning culture described in literature has been put into practice in regional development. The study firstly works out the key aspects of a new planning culture by identifying them in the relevant literature. Then these aspects are analysed with the help of own empirical works with regards to the practice of regional development. The article concludes with a statement on the actual presence of a new planning culture in the practice of regional development.